ANALISIS DAN MITIGASI RISIKO RANTAI PASOK PADA PEKERJAAN TANAH TIMBUNAN PROYEK KONSTRUKSI JALAN DENGAN METODE FMEA - Taufiq Arya Putra N; Fitri Nugraheni (JURNAL ILMIAH NUSANTARA, 2025)
Success in completing construction projects is influenced by many factors that are mutually dependent on each other, one of which is the supply chain. In 2018, the Public Works and Spatial Planning Department of West Sumatra Province, Indonesia had 24 road construction work packages. Only 33.3% were completed on time and the remaining 66.7% experienced delays, one of which was due to material delays (Rita et al., 2021). Embankment work on the Solo – Yogyakarta – YIA Kulon Progo Toll Road Project Section I Package 1.2 cannot be separated from the potential for delays. The supply chain is a special concern for this project, because the large material requirements and the difficulty of finding landfill material that meets specifications can become obstacles if the risks in each process are not managed well. The instrument used is Failure Mode and Effect Analysis (FMEA), namely by identifying failures in each process and the impacts that can occur on the activities carried out, so that mitigation actions can be determined to minimize risks that may occur. The research results showed that there are 5 supply chain activities for earth embankment work, namely raw materials, suppliers, manufacturing, distribution and consumers. There are 41 risks divided into 3 risk levels. At the raw material stage there are 4 medium risks and 2 high risks, at the supplier stage there are 7 medium risks, at the manufacturing stage there is 1 low risk and 6 medium risks, at the distribution stage there are 2 low risks and 11 medium risks, and at the consumer stage there are 8 moderate risk. There are 47 control measures which are divided into 5 aspects, namely Man, Money, Machine, Material and Method.